Strokovne novosti in izvajanje zakona o obveznem izvodu publikacij - Sešek, Irena (Knjižnica, 2006)
The article presents the most important professional novelties introduced by the new Legal Deposit Law and assesses the state of implementation. The new Law changes legal deposit in three significant respects: (1) legal deposit is extended to online electronic publications, (2) publishers must deliver legal deposit copies instead of printers, (3) the number of legal deposit copies has been decreased to four from the previous sixteen. These changes ensure that some deficiencies of the previous Law, which caused that the Slovenian written cultural heritage was being less comprehensively collected, have been corrected. Legal Deposit Law also introduces a new group of publications, which have been financed or co-financed by public funds (EU, state or local resources). Sixteen copies of these publications are required to be deposited with the National and University Library, which distributes fourteen copies to other legal deposit libraries. The novelties also bring some changes to the tasks of collecting, processing, organizing, preserving, using and weeding of legal deposit copies. Therefore, it will be necessary to provide human and technical resources in the legal deposit organisations to ensure effective implementation of the Law, and collection and preservation of the cultural heritage.
Keywords: obvezni izvod; elektronske publikacije; pravna ureditev; Slovenia; Slovenija; založništvo; library science; bibliotekarstvo